The Diagnosis and Prognosis Value of Circulating Exosomal lncRNA MALAT1 and LNC_000226 in Patients With Acute Myocardial Infarction: An Observational Study - Xiaodong Gu; Jingyuan Hou; Ruiqiang Weng; Jiawei Rao; Sudong Liu (Immunity, Inflammation and Disease)
ABSTRACT Background Acute myocardial infarction (AMI) stands as a leading cause of global morbidity and mortality. This study aims to explore the potential roles of circulating exosomal lncRNA MALAT1 and LNC_000226 in AMI diagnosis and prognosis. Methods This retrospective observational study included 90 patients with AMI and 88 patients with normal coronary artery (NCA). Plasma exosomes were isolated via ultracentrifugation, and the levels of exosomal lncRNA MALAT1 and LNC_000226 were examined using qRT‐PCR. Major adverse cardiovascular events (MACEs) that occurred during 1‐year follow‐up post‐stent implantation were collected. The diagnostic value of exosomal MALAT1 and LNC_000226 was determined by receiver operating characteristic (ROC) analysis. The association between exosomal LNC_000226 and MACEs was assessed by Kaplan–Meier and Cox regression analysis. Results Both lncRNA MALAT1 and LNC_000226 levels in plasma exosomes were elevated in AMI patients compared to NCA controls. Moreover, LNC_000226 (AUC: 0.889, sensitivity: 82%, specificity: 72%) exhibited superior diagnostic performance compared to MALAT1 (AUC: 0.707, sensitivity: 71%, specificity: 57%). During 1‐year follow‐up period, the incidence of MACEs was significantly higher among patients with high exosomal LNC_000226 levels compared to those with low exosomal LNC_000226 levels [64% (29/45) vs. 40% (18/45), p < 0.05]. Multivariable Cox regression analysis revealed a positive association between exosomal LNC_000226 level and the risk of MACEs in AMI patients (HR: 1.959, 95% CI: 1.040–3.689). Conclusion Circulating exosomal lncRNA MALAT1 and LNC_000226 are promising biomarkers for diagnosing AMI, with LNC_000226 potentially indicating a prognosis.